Wireless sensor placement based on SHM requirements and net energy consumption - Onoufriou, Toula; Soman, Rohan N.; Han, Βo; Chrysostomou, Christis; Votsis, Renos; Kyriakides, Marios (My University, 2012)
Structural Health Monitoring (SHM) techniques have undergone a paradigm shift due to new emerging technologies and developments in the field of remote communications. The use of Wireless Sensor Networks (WSN) has been on an increase in the last decade due to its low cost deployment, ease of maintenance and increased efficiency. However, the battery life of the sensors of such networks is limited and hence puts severe restrictions on the use of this technology. Thus there is a need to enhance the life time of the network through optimizing the energy usage of sensors. This can be achieved through the use of energy harvesting using ambient vibrations. However, if the sensor placement is carried out for achieving network longevity alone, it might lead to loss of vital information, thus making the sensor placement useless from the SHM perspective. This paper focuses on optimizing the location of the sensors to cater to the specific requirements of structural engineering while adhering to the energy limitations imposed due to the use of WSN. In this paper an Optimal Sensor Placement problem taking into consideration the application demands and the net energy usage of the sensor is formulated and solved making use of Genetic Algorithm for a near optimal solution.
Keywords: Wireless sensor networks; Structural health monitoring; Force and energy